Non-rhinoplastic techniques for the reconstruction of trans- surgical defects in the nasal dorsum. Review article - Pedroso Acosta, Griselda (2023)
The face for many centuries, has represented the focus of appearance. The middle facial third is its most important area and is therefore extremely vulnerable to facial deformities. Within it, the nose is the most important facial prominence. From years ago, his deformities were considered a curse, so many men were condemned to death. From this moment, the nasal reconstruction boom increases, and, currently, the evolution of techniques in nasal reconstruction is an extremely useful option to repair facial defects of any size. This review intends to update information on non-rhinoplastic techniques for the reconstruction of trans-surgical defects on the nasal dorsum. An evaluation of the available bibliography and previous research on the topic was carried out in the period from May 2018 to May 2023. 31 popular science magazines were considered. Articles published in English, Italian and Spanish were prioritized. The Pubmed, Ebsco, SciELO y Scopus databases were consulted. Of the 95 articles reviewed, the study was limited to 43 of them. Among the non-rhinoplasty techniques reviewed were healing by secondary intention, primary closure, grafts and flaps. There are factors that influence the selection of one or the other, such as: the diameter of the defect, its depth, location, texture and contour of the skin, mastery and professionalism of the surgeon, among others. There is no consensus on a technique of choice. With all of them, favorable results can be achieved by making a good selection and application of it.